Determinasi Faktor Ekonomi, Sosial, dan Teknis terhadap Pergeseran Pekerjaan Petani Padi (Studi Kasus di Kabupaten Malinau) - Zulhafandi Zulhafandi; Flories Tamara Rizki; Mohammad Wahyu Agang; Muhammad Arbain; Hendris Hendris (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2025)
Changing professions is a process in which a person switches from one job or profession to another, often for a significantly different job, driven by factors such as population growth, demands for basic materials, especially rice, and the need for rice plants. This study aims to identify and understand the factors influencing the occupational shift among rice paddy farmers in Nunukan Regency (Case Study: Mansappa Village, South Nunukan District). The sampling technique used in this research is the census method, involving 30 respondents who shifted from rice paddy farming to seaweed cultivation. The research data were analyzed using quantitative descriptive methods, validity and reliability tests, classical assumption testing, coefficient of determination (R²), multiple linear regression, F-test, and t-test. The factors influencing the occupational shift of rice paddy farmers include economic, social, and technical factors, supported by indicators such as price, income, marketing, social environment, family, government policy, climate, and crop cultivation. The analysis yielded an R² value of 29.1%, with the multiple linear regression equation: Y = 3.839 + 0.250 X₁ + 0.538 X₂ + 0.124 X₃. The F-test showed that economic, social, and technical factors simultaneously influence the occupational shift of rice paddy farmers in Nunukan Regency. Based on the t-test, Social factors have a significant influence on the transition of rice farmers' professions in Nunukan Regency (p-value = 0.036).